Anti-inflammatory and immunomodulatory properties of Carica papaya. (3rd July 2016) - Pandey, Saurabh; Cabot, Peter J.; Shaw, P. Nicholas; Hewavitharana, Amitha K.
Abstract: Chronic inflammation is linked with the generation and progression of various diseases such as cancer, diabetes and atherosclerosis, and anti-inflammatory drugs therefore have the potential to assist in the treatment of these conditions. Carica papaya is a tropical plant that is traditionally used in the treatment of various ailments including inflammatory conditions. A literature search was conducted by using the keywords "papaya", "anti-inflammatory and inflammation" and "immunomodulation and immune" along with cross-referencing. Both in vitro and in vivo investigation studies were included. This is a review of all studies published since 2000 on the anti-inflammatory activity of papaya extracts and their effects on various immune-inflammatory mediators. Studies on the anti-inflammatory activities of recognized phytochemicals present in papaya are also included. Although in vitro and in vivo studies have shown that papaya extracts and papaya-associated phytochemicals possess anti-inflammatory and immunomodulatory properties, clinical studies are lacking.